Volatiles extracted from Melaleuca Rugulosa (Link) Craven leaves: comparative profiling, bioactivity screening, and metabolomic analysis - Mohamed S. Mady; Heba E. Elsayed; Nashwa F Tawfik; Fatma A. Moharram (BMC Complementary Medicine and Therapies)
Abstract Background Melaleuca species (family Myrtaceae) are characterized by their wide-ranging applications as antimicrobials and in skin-related conditions. Herein, we estimated the volatile profile and biological significance of M. rugulosa (Link) leaves for the first time supported by a dereplication protocol. Materials and methods Volatile components were extracted using hydrodistillation (HD), supercritical fluid (SF), and headspace (HS) techniques and identified using GC/MS. The variations among the three extracts were assessed using principal component analysis and orthogonal partial least square discriminant analysis (OPLS-DA). The extracted volatiles were tested for radical scavenging activity, anti-aging, and anti-hyperpigmentation potential. Finally, disc diffusion and broth microdilution assays were implemented to explore the antibacterial capacity against Streptococcus pyogenes, Staphylococcus aureus, Clostridium perfringens, and Pseudomonas aeruginosa. Results The yield of the SF technique (0.8%) was three times higher than HD. GC/MS analysis revealed that the oxygenated compounds are the most proponents in the three extracts being 95.93% (HD), 80.94% (HS), and 48.4% (SF). Moreover, eucalyptol (1,8-cineol) represents the major component in the HD-EO (89.60%) and HS (73.13%) volatiles, while dl-α-tocopherol (16.27%) and α-terpineol (11.89%) represent the highest percentage in SF extract. Regarding the bioactivity profile, the HD-EO and SF-extract showed antioxidant potential in terms of oxygen radical absorbance capacity, and β- carotene assays, while exerting weak activity towards DPPH. In addition, they displayed potent anti-elastase and moderate anti-collagenase activities. The HD-EO exhibited potent anti-tyrosinase activity, while the SF extract showed a moderate level compared to tested controls. OPLS-DA and dereplication studies predicted that the selective antibacterial activity of HD-EO to S. aureus was related to eucalyptol, while SF extract to C. perfringens was related to α-tocopherol. Conclusions M. rugulosa leaves are considered a vital source of bioactive volatile components that are promoted for controlling skin aging and infection. However, further safety and clinical studies are recommended.